Application of Adobe Premiere-Based Video Learning Media to Progress Understudy Learning Results at SMP Negeri 18 Bulukumba - Muh. Syilfa Nooviar; Nur Fahmi Akhmad; Asri (Yayasan Cendekiawan Digital Indonesia (CEDDI), 2023)
This study aims to improve 18 Bulukumba learning outcomes of high school students through the use of educational videos in Adobe Premiere pro. The type of research used in this study is classroom research. The study was carried out in two cycles of data collection through experimentation, observation and recording, Actions, Plan, Do, Observe and Reflect, each of 2 parts. The collected data were then analyzed using descriptive analysis. Based on the findings of the study, it can be concluded that the Adobe Premiere Pro-based educational video environment application can improve students' learning. According to the study of Improving Student Learning Achievement in the 1st Cycle, 72.8, 14 students had a 56% success rate. then cycle II averaged 91.7, the frequency of learning completeness was 22 students with a percentage of completeness of 88%. passed the KKM standard for class VII.A/1 students of junior high school 18 Bulukumba.